Tinjauan Hukum Islam Tentang Pemanfaatan Harta Waris Secara Bersama - Syaripudin, Enceng Iip; Mubarok, Fahmi Farhan (Jurnal Hukum Ekonomi Syariah, 2025)
Inheritance is the right of every individual heir. Heirs are free to determine the use of the inheritance that is their share individually without having to be bound to other heirs. However, in practice in the Jati Village community there are inheritances that are used together. The purpose of this study is to see the mechanism of joint utilization of inheritance assets carried out by the people of Jati Village, Tarogong Kaler District, Garut Regency from an Islamic Law perspective. This research will focus on data from the field (field research) with a qualitative approach. Data is obtained through interviews, observations, and other supporting data related to the subject and object of research. The results of the study indicate that there are two practices of joint utilization of inheritance assets carried out by the Jati Village community, namely rotating rice fields and joint management of inheritance assets before they are distributed. This practice does not conflict with Islamic law. because it is carried out based on an agreement with the aim of maintaining the integrity and harmony of the family, as well as ensuring mutual welfare and in line with the principle of willingness and helping each other in goodness. However, it is better if this practice is carried out after the distribution of inheritance assets or at least each heir knows their share.  Keyword : Islamic law, property, inheritance